CHINA’S SHIFTING BEHAVIOUR TOWARDS SOUTH KOREA IN THAAD CRISIS RESOLUTION IN KOREAN PENINSULA - M. Ganang Wira Pradana (Jurusan Ilmu Hubungan Internasional, 2021)
ABSTRACTThe THAAD crisis between South Korea and China occurred due to the installation of the THAAD (Terminal High Altitude Area Defense) system by South Korea with the help of the United States which was considered as a threat to China's national security. China strongly opposed the installation of the defense system and imposed unofficial sanctions in a form of a boycott in the field of South Korean tourism, products, and pop culture, which provided significant losses due to China's retaliation. After the South Korean state visit to China which was held in Beijing, China’s boycott was later lifted, but the THAAD installed in South Korea remain stayed and deployed. Thus the question arises about why China chose to soften and not force the South Koreans to withdraw THAAD. This article uses the qualitative research method of literature studies and uses variables of foreign policy theory by Yuen Foon Khong as the theoretical framework in this paper. Therefore, it can be seen that China's softening of the THAAD issue is caused by the influence of China’s